Collagenase Clostridium histolyticum for the Treatment of Peyronie's Disease: The Development of This Novel Pharmacologic Approach. (5th May 2015) - Gelbard, Martin K.; Chagan, Larisa; Tursi, James P.
Abstract Introduction The conception of collagenase Clostridium histolyticum (CCH) as treatment for Peyronie's disease (PD) was a vital first step in providing a nonsurgical, minimally invasive FDA‐approved treatment for men with PD. Aim To review the origins, clinical research history, and ultimately FDA approval of collagenase as PD treatment. Methods A PubMed search using (Peyronie's or Peyronie) AND collagenase, and limited to clinical research studies, returned nine papers that were examined in the current review. Results Collagenase as a PD treatment arose in response to a lack of effective nonsurgical treatments and the incomplete understanding of underlying PD etiology. Awareness of dense collagen in PD scarring and parallel initial exploration of collagenase to treat herniated lumbar discs coincided with and inspired laboratory‐based investigation of collagenase effects on excised PD plaque tissue. The foundational conceptual work and the critical development of purified injectable collagenase allowed the pursuit of clinical studies. Progression of clinical studies into large‐scale robust trials culminated in two important outcomes: development of the first validated, PD‐specific measure of psychosexual function, the Peyronie's Disease Questionnaire, and the first FDA‐approved treatment for PD. Conclusions Collagenase therapy began as an attempt to modify the structure of PD‐related tunica albuginea scarring, despite the lack of a fundamental understanding of the scar's origin. If we wish to advance PD treatment beyond this first effective step, the future needs to bring us full circle to the starting point: We need a greater understanding of the control of collagen deposition and wound healing in men with PD. Gelbard MK, Chagan L, and Tursi JP. Collagenase Clostridium histolyticum for the treatment of Peyronie's disease: The development of this novel pharmacologic approach. J Sex Med 2015;12:1481–1489.